PERISTILAHAN DALAM PENGOBATAN TRADISIONAL SUKU DAYAK BENAWAN - Roimondo Roimondo; Sisilya Saman Madeten; Patriantoro Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to describe the terminology of Dayak Benawan traditional medicational, to describe a lexical and cultural meaning, and to implement it in the learning activity. Dayak Benawan vernacular is one of several Dayak sub-tribe vernaculars that develop in Kabupaten Sanggau. The researcher interested to analyze Dayak Benawan’s vernacular which has a characteristic in the terminology of traditional medication, which was used the traditional medium. The purpose of this research was to conserve Dayak Benawan’s vernacular. This study was a quantitative research with descriptive method. The data were the words from respondents that related to medium in the procession which was clause and phrase used in Dayak Benawan traditional medication. Data collection techniques were used interviews, giving hints, one-to-one interviews, recording audio, and taking notes techniques, the instruments were used questionnaire, recording tool, and field notes. The result shows that there were 42 terminologies which clarified as clauses and phrases. In Dayak Benawan's traditional medicament, there were 25 data of medium terminology and 17 data of medication terminology. Keywords: Traditional Medication, Lexical Meaning, Cultural  Meaning, Procession.